2013
DOI: 10.1093/jpepsy/jst053
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Posttraumatic Stress Following Pediatric Injury: A Randomized Controlled Trial of a Web-Based Psycho-Educational Intervention for Parents

Abstract: Brief web-based interventions introduced during child hospitalization are a feasible strategy to reach many parents following pediatric injury. Preventing psychological symptoms may require more than parental education alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 38 publications
2
52
0
3
Order By: Relevance
“…Although there is evidence to suggest having both parents attend intervention sessions together is important for facilitating skill development (Tiano & McNeil, ) and better mental health outcomes (May et al, ), the current results suggest interventions might be improved by incorporating content that is specific to the symptoms (e.g., depressed mood and motivation) and stressors (e.g., more strategies around work‐related issues for fathers). In addition, parental interventions in the context of a child's serious illness or injury are often conducted acutely, that is, while the child is an inpatient (Fedele et al, ; Melnyk et al, ; Sahler et al, ), or in the months following the acute period (Burke et al, ; Marsac et al, ). Results presented here suggest that after the initial diagnosis phase, overall parents report psychological symptoms in the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence to suggest having both parents attend intervention sessions together is important for facilitating skill development (Tiano & McNeil, ) and better mental health outcomes (May et al, ), the current results suggest interventions might be improved by incorporating content that is specific to the symptoms (e.g., depressed mood and motivation) and stressors (e.g., more strategies around work‐related issues for fathers). In addition, parental interventions in the context of a child's serious illness or injury are often conducted acutely, that is, while the child is an inpatient (Fedele et al, ; Melnyk et al, ; Sahler et al, ), or in the months following the acute period (Burke et al, ; Marsac et al, ). Results presented here suggest that after the initial diagnosis phase, overall parents report psychological symptoms in the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have shown that their interventions, in addition to reducing post‐traumatic stress symptoms, brought other benefits such as improvement in mother‐infant interactions quality, increase in maternal sensitivity and infant cooperation during interactions (Borghini et al., ), as well as a decrease in anxiety and depression (Shaw et al., ), improvement in parental psychological flexibility and mindfulness (Burke et al., ) and decrease prolonged grief symptoms (Kersting et al., ). However, some authors reported no effects of the Internet‐based intervention (Galvin & Muscara, ; Marsac et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Some incorporated other psychotherapeutic approaches, for example, motivational interviewing [29] or parenting guidance [33,49], in addition to CBT techniques. Others included additional elements of expressive writing, sometimes about a stressful event or trauma, but did not state that they supported participants to cognitively reappraise their reactions or provide any further therapeutic instruction focused on the trauma [30,31,36,47,51].…”
Section: Resultsmentioning
confidence: 99%